The use of the internet in the development of speaking - Marková, Aneta (Univerzita Pardubice, 2011)
This diploma thesis deals with the possible use of the internet in the development of language productive skill of speaking. In the theoretical part the Thesis discusses communicative competence, theory of speaking, different types of practice and activities suitable for the development of speaking, and the internet and its potential in the development of these skills. The empirical part focuses on several designed internet-based speaking activities which are applied to a particular group of basic school learners and subjected to critical evaluation.
Využití internetu při rozvoji řečové dovednosti mluvení
Keywords: komunikativní kompetence; komunikativní výuka jazyků; řečové dovednosti; řečové aktivity; mluvní projev; metodologie výuky anglického jazyka; communicative competence; communicative language teaching; speaking; speaking activities; internet; ELT methodology